CONSUMERISM IN COSMETICS INDUSTRY: THE CASE STUDY OF CORPORATE SOCIAL RESPONSIBILITY PRACTICES OF THE BODY SHOP IN PAKISTAN - Hasan, Rachel Aruna (PEOPLE: International Journal of Social Sciences, 2018)
Cosmetics industry is the world's largest multi-billion dollar rapidly growing industry. Consumerism in cosmetics is a growing phenomenon that needs to be investigated from the perspective of social ethics. With growing public awareness and demand for socially responsible businesses of cosmetics, nowadays companies take Corporate Social Responsibility into account when planning future socially responsible business operations in different parts of the world. It is an issue that has taken importance in business functions and is taken very seriously. This research article examines one such case study of corporate social responsibility exemplified by The Body Shop in Pakistan. The objective was to gauge whether the consumers are aware of the corporate social responsibilities of the brands, especially the cosmetics brands. A survey is conducted from (N= 100) respondents through a well-structured questionnaire by convenience sampling from the consumers of The Body Shop located in Lahore, Pakistan. The respondents are approached as those who are users of the brand; those who visited the outlet for purchases. The findings of the study reveal that most of the consumers of The Body Shop in Pakistan are aware that the brand follows CSR as its key business function. The brand poses its responsibility towards the society by practicing corporate citizenship and philanthropic aspects. The study has theoretical and business development implications.